Biological Activity of Titania Nanopowder using Atmospheric Pressure Plasma Jet Technique - Mahmood, Mustafa; Hammudi, Riyam; Odah, Jafer; Chaloob, Walaa (Indonesian Journal Publisher, 2025)
In this work, titanium dixide Nano powder were synthesized by atmospheric pressure plasma jet. The study initiates with the exploitation of atmospheric pressure plasma jet technique recognized for its capability to generate nanoparticles using cold plasma, ensuring high purity and controlled growth. The average particle size and morphology have been examined by FE-SEM and the crystallinity was estimated by XRD analysis and the spectroscopic properties of the powder has neen measured by using FTIR spectroscopy. XRD studies confirm the titanium dioxide have a high degree of crystallinity. Their particle size of TiO2 was found about 22 nm. The purpose of these study involve the studying of TiO2 nanoparticles characteristic. The outcome considered a new synthesis of TiO2 nanopowders to employ in many scientific applications using continuous laser diode to increase the oxidization represent as a novel method. It is a simple and cost effective method.